2018
DOI: 10.1111/jonm.12717
|View full text |Cite
|
Sign up to set email alerts
|

The trouble with reporting and utilization of workplace violence data in health care

Abstract: Staff should be encouraged to complete incident reports for each episode of workplace violence. Incident reporting systems must be simplified to reduce the burden of reporting. Nurse managers should advocate for the sharing of health service workplace violence data, to enable improved prevention across all services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…However, while the nurses in this study discussed how they wanted more counselling and debriefing, they particularly encountered difficulties with the complexity of reporting. Accurate reporting is important for devising effective workplace interventions, and simplified methods of reporting violence would increase staff compliance with communicating violent incidents (Morphet, Griffiths, Innes et al., 2019). Dafny and Beccaria (2020) indicate that few cases are reported due to lack of time, lengthy complicated forms (including a lack of training in how to complete them), lack of follow through and feedback from management and a sense that only physical violence is viewed as reportable.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the nurses in this study discussed how they wanted more counselling and debriefing, they particularly encountered difficulties with the complexity of reporting. Accurate reporting is important for devising effective workplace interventions, and simplified methods of reporting violence would increase staff compliance with communicating violent incidents (Morphet, Griffiths, Innes et al., 2019). Dafny and Beccaria (2020) indicate that few cases are reported due to lack of time, lengthy complicated forms (including a lack of training in how to complete them), lack of follow through and feedback from management and a sense that only physical violence is viewed as reportable.…”
Section: Discussionmentioning
confidence: 99%
“…9 The present study suggested that emergency nurses do not feel safe at work, which may in part be due to the lack of a hospital policy for reporting WPV and the perceived barriers to reporting WPV. An efficient reporting system is a critical component of a prevention strategy against WPV, 12 and multiple forms of communication have been suggested recently to diminish the barriers to reporting WPV. 13 Two studies of Taiwanese emergency nurses indicated that WPV not only caused emotional and physical injuries but also might drive nurses away from emergency nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative research has found that inconsistencies in reporting guidelines, normalization of violence, and challenges with reporting procedures have all contributed to the underreporting of violence in healthcare settings (Morphet et al . 2019). An additional, survey‐based investigation found that fear of job loss and belief that reporting would do little to ameliorate the problem are also contributing factors (Kvas & Seljak 2014).…”
Section: Summary Assessment Of Study Strengths and Weaknessesmentioning
confidence: 99%